Selective functionalization of the 1H-imidazo[1, 2-b]pyrazole scaffold. A new potential non-classical isostere of indole and a precursor of push–pull dyes. Issue 39 (10th September 2021) - Schwärzer, Kuno; Rout, Saroj K.; Bessinger, Derya; Lima, Fabio; Brocklehurst, Cara E.; Karaghiosoff, Konstantin; Bein, Thomas; Knochel, Paul
Abstract : A methodology for the selective functionalization of the 1 H -imidazo[1, 2- b ]pyrazole scaffold has been developed and used in the synthesis of novel push–pull dyes and a non-classical isostere of the indolyl drug pruvanserin. Abstract : We report the selective functionalization of the 1 H -imidazo[1, 2- b ]pyrazole scaffold using a Br/Mg-exchange, as well as regioselective magnesiations and zincations with TMP-bases (TMP = 2, 2, 6, 6-tetramethylpiperidyl), followed by trapping reactions with various electrophiles. In addition, we report a fragmentation of the pyrazole ring, giving access to push–pull dyes with a proaromatic (1, 3-dihydro-2 H -imidazol-2-ylidene)malononitrile core. These functionalization methods were used in the synthesis of an isostere of the indolyl drug pruvanserin. Comparative assays between the original drug and the isostere showed that a substitution of the indole ring with a 1 H -imidazo[1, 2- b ]pyrazole results in a significantly improved solubility in aqueous media.